STRATEGI KEBIJAKAN PENANGANAN STUNTING PROPINSI JAWA BARAT DI MASA PANDEMI COVID 19 (ANALISIS IMPLEMENTASI DAN SOLUSI) STRATEGY OF STUNTING HANDLING POLICY IN WEST JAVA PROVINCE DURING THE COVID-19 PANDEMI (ANALYSIS OF IMPLEMENTATION AND SOLUTION) - Lia Fitrianingrum (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2022)
ABSTRACT Stunting in Indonesia has an equitably high prevalence. Indonesia is projected to experience peak productive population growth with a demographic bonus in 2035. However, this demographic bonus will not be useful or will even become a state burden if current under five high prevalence of stunting is not corrected. Stunting causes economic losses of 2-3% of Gross Domestic Product (GDP). Based on world bank data, Indonesia's GDP was 13,000 trillion in 2017, so the loss due to stunting was estimated at 260-390 trillion. Role of each region in contributing to stunting rates is also diverse, one of which is West Java Province, one of the provinces with the largest population in Indonesia. Efforts to reduce stunting rate in West Java have become even more difficult during the COVID-19 pandemic, where 83.9% of immunization services are estimated to be disrupted, and it is also estimated that the stunting rate will increase after this pandemic. Therefore, it is necessary to analyse the implementation strategy of stunting handling policy in West Java Province. The purpose of this study was to explore the real conditions of the policy implementation, so that it could be input to relevant stakeholders. This study used a qualitative approach. Data collection techniques were carried out by collecting secondary data, observation, and interviews. The results of the study showed that the content, process, context, and actors as the elements in the implementation of stunting handling policies in West Java worked in synergy with each other. Besides the four elements, leadership was another very important element. Leadership in West Java really determined the optimal role of content, process, context, and actors’ elements.Keywords: strategy, policy implementation, stunting, West Java Province